International Photographic Classification and Grading System for Myopic Maculopathy - Ohno-Matsui, Kyoko; Kawasaki, Ryo; Jonas, Jost B.; Cheung, Chui Ming Gemmy; Saw, Seang-Mei; Verhoeven, Virginie J.M.; Klaver, Caroline C.W.; Moriyama, Muka; Shinohara, Kosei; Kawasaki, Yumiko; Yamazaki, Mai; Meuer, Stacy; et al. (American journal of ophthalmology, 2015)
To develop a classification and grading system for myopic maculopathy. Development and evaluation of a classification system for myopic maculopathy based on observational case series. A comprehensive set of myopic macular lesions was defined via literature review and through consensus meetings among retinal specialists and clinician scientists. A classification of myopic maculopathy was formulated based on fundus photographs and a modified Delphi process and consensus. Inter- and intraobserver reproducibility, assessed as agreement (%) and weighted kappa values, were evaluated. One hundred retinal photographs with myopia and myopic macular lesions were selected from case series at the High Myopia Clinic of the Tokyo Medical and Dental University, Tokyo, Japan. We defined 5 categories of myopic maculopathy including “no myopic retinal degenerative lesion” (Category 0), “tessellated fundus” (Category 1), “diffuse chorioretinal atrophy” (Category 2), “patchy chorioretinal atrophy” (Category 3), and “macular atrophy” (Category 4). Three additional features to supplement these categories were defined as “plus” lesions, namely, lacquer cracks, myopic choroidal neovascularization, and Fuchs spot. Posterior staphyloma was considered as a further, important sign of myopic retinopathy. The intraobserver agreement was ≥85% and the corresponding weighted kappa statistic was ≥0.6 between observations. After a brief training session, interobserver kappa statistics reached the predefined satisfactory level (≥0.4), considered as above moderate agreement. We propose a classification system for myopic maculopathy that was found to be reproducible. Applying a uniform classification in different studies will facilitate communication and comparison of findings from clinical trials and epidemiologic studies.